MOBILIZATION OF PLANT GENETIC RESOURCES FROM THE TERRITORIES OF INDONESIA, SRI LANKA (CEYLON) AND NEPAL - N. P. Loskutova; T. M. Ozerskaya (Труды по прикладной ботанике, генетике и селекции)
The article is dedicated to the mobilization of plant genetic resources from the territories of Indonesia, Sri Lanka (Ceylon) and Nepal to VIR’s collection by means of collecting explorations, germplasm requests and the exchange of accessions. The first, the longest and the only pre-war expedition to Indonesia and Ceylon was undertaken by Prof. V. V. Markovich; it lasted three years (1926–1928). He explored Java, Singapore and Ceylon, where he collected 772 germplasm samples. In 1957, D. V. Ter-Avanesyan, who worked as an agricultural attaché at the USSR Embassy in India, familiarized himself in every detail with plant resources and agriculture in Nepal. The late 1960s were marked by intensification of plant genetic resources introduction and new opportunities to organize regular collecting missions. In the period from 1960 to 1991, there were five plant exploration trips to Indonesia, Sri Lanka (Ceylon) and Nepal. In 1960, D. V. Ter-Avanesyan visited scientific institutions in Java, got acquainted with the main trends in agriculture, and collected 302 plant samples. In 1974, A. G. Lyakhovkin took part in a specialized collecting mission launched to study and collect wild forms and cultivars of rice and various other crops from Nepal. The team visited 16 experiment stations and farms and collected 1170 accessions. In 1985, an expedition team led by E. F. Molchanov collected and studied wild and cultivated forms of subtropical plants in Sri Lanka. The team visited 5 institutes and experiment stations, 3 botanical gardens, and collected 370 accessions. In 1988, another collecting team led by L. A. Burmistrov, whose task was to study the system of nation-wide projects on crop improvement, traveled over four provinces, visited 11 scientific and academic institutions of Nepal, and collected 766 germplasm samples. The last collecting trip to Indonesia was led by N. G. Musatenko in 1991. The team collected 95 varieties and wild forms. In total, the Institute’s collecting and exploration activities in Indonesia, Sri Lanka (Ceylon) and Nepal added 3496 accessions to its collections. In addition to direct collecting in Indonesia, Sri Lanka (Ceylon) and Nepal, VIR has always been replenishing its holdings by seed requests. During the whole pre-war period, from 1925 through 1941, 256 germplasm accessions were added. All in all, from 1948 through 2018, 104 accessions were introduced from Indonesia, Sri Lanka (Ceylon) and Nepal. The greatest number of accessions received by the Institute represented groat crops (over 1400), followed by wheat and barley (458), and industrial crops (627). In total, during the whole period of its existence, the Institute has mobilized 3843 accessions, representing 377 plant species.